A restatement of the natural science evidence base concerning the health effects of low-level ionizing radiation. Issue 1862 (13th September 2017) - McLean, Angela R.; Adlen, Ella K.; Cardis, Elisabeth; Elliott, Alex; Goodhead, Dudley T.; Harms-Ringdahl, Mats; Hendry, Jolyon H.; Hoskin, Peter; Jeggo, Penny A.; Mackay, David J. C.; Muirhead, Colin R.; Shepherd, John; et al.
Abstract : Exposure to ionizing radiation is ubiquitous, and it is well established that moderate and high doses cause ill-health and can be lethal. The health effects of low doses or low dose-rates of ionizing radiation are not so clear. This paper describes a project which sets out to summarize, as a restatement, the natural science evidence base concerning the human health effects of exposure to low-level ionizing radiation. A novel feature, compared to other reviews, is that a series of statements are listed and categorized according to the nature and strength of the evidence that underpins them. The purpose of this restatement is to provide a concise entrée into this vibrant field, pointing the interested reader deeper into the literature when more detail is needed. It is not our purpose to reach conclusions on whether the legal limits on radiation exposures are too high, too low or just right. Our aim is to provide an introduction so that non-specialist individuals in this area (be they policy-makers, disputers of policy, health professionals or students) have a straightforward place to start. The summary restatement of the evidence and an extensively annotated bibliography are provided as appendices in the electronic supplementary material.